Population growth, prey preference and pest control potential of three predatory bugs species (Hem.: Miridae), natural enemies of T. absoluta (Lep.: Gelechiidae) - Pereira, Ana Maria Calixto (2015)
Tomato borer Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), tomato fruit borer Neoleucinodes elegantalis (Gueéne) (Lepidoptera: Crambidae) and Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) are important pests and can be responsible for major damages and economic losses in tomato crops if no control is used. The main control for these pests in Brazil is chemical, while in Europe, the mirid predators Macrolophus pygmaeus (Rambur) and Nesidiocoris tenuis (Reuter) (Hemiptera: Miridae) are commercialized and used to control T. absoluta. Recently, in Brazil, three species of mirid predators [Campyloneuropsis infumatus (Carvalho), Engytatus varians (Distant) and Macrolophus basicornis (Stal)] were found, having been evaluated regarding biological and behavioral traits, as well as potential use against T. absoluta and other tomato crop pests. In this study, we evaluated (1) the effect of different temperatures over the reproduction, longevity and population growth parameters (rm, R0, λ, T, DT) of C. infumatus, E. varians and M. basicornis;, (2) prey preferences for T. absoluta, N. elegantalis and H. armigera, in addition to predation behavior when having T. absoluta and N. elegantalis as prey in chance and no-choice tests, and; (3) evaluate population dynamics against T. absoluta in greenhouse experiment. The results showed that temperature affected the reproductive parameters of C. infumatus, E. varians and M. basicornis. The optimal temperature range for reproduction and longevity ranged from 24°C to 28°C. Prey preference tests indicated that the predators were able to prey on T. absoluta, N. elegantalis and H. armigera in no-choice tests. In choice tests, the predators had preference for T. absoluta. In the population dynamics tests against T. absoluta, C. infumatus and M. basicornis were able to establish and reproduce in tomato plants, decreasing the population of T. absoluta. E. varians was not able to establish in tomato plants within greenhouse conditions. The best release rate at the evaluated conditions was of two couples of mirid predators per plant. Predators C. infumatus and M. basicornis did not damage the tomato plants. Predators C. infumatus and M. basicornis have potential as good candidates for the biological control of T. absoluta and other tomato crop pests.